2024
DOI: 10.1002/jbm.a.37677
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for drug‐resistant Pseudomonas aeruginosa: Metal and metal oxide nanoparticles

Yujuan Zhan,
Huiting Hu,
Ying Yu
et al.

Abstract: Pseudomonas aeruginosa (PA) is a widely prevalent opportunistic pathogen. Multiple resistant strains of PA have emerged from excessive or inappropriate use of antibiotics, making their eradication increasingly difficult. Therefore, the search for highly efficient and secure novel antimicrobial agents is crucial. According to reports, there is an increasing exploration of nanometals for antibacterial purposes. The antibacterial mechanisms involving the nanomaterials themselves, the release of ions, and the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…252,253 Therefore, a combined mechanism is initiated against eliminating bacteria; hence, the potency of IONPs increases. 254 Additionally, surface modification approaches can help address IONPs' main drawbacks, such as stability issues, cytotoxicity, biocompatibility, and moderate antibacterial activity. 149,255 Biopolymers such as PEG and chitosan are used as coating material to modify the surface of IONPs.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…252,253 Therefore, a combined mechanism is initiated against eliminating bacteria; hence, the potency of IONPs increases. 254 Additionally, surface modification approaches can help address IONPs' main drawbacks, such as stability issues, cytotoxicity, biocompatibility, and moderate antibacterial activity. 149,255 Biopolymers such as PEG and chitosan are used as coating material to modify the surface of IONPs.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Though IONPs have several limitations as therapeutic agents, these limitations can be minimized using biocompatible precursors and surface modification. For instance, in the GRS synthesis method, bioreductants, which consist of phytochemicals with prior antimicrobial activity, are used instead of chemicals. , Therefore, a combined mechanism is initiated against eliminating bacteria; hence, the potency of IONPs increases . Additionally, surface modification approaches can help address IONPs’ main drawbacks, such as stability issues, cytotoxicity, biocompatibility, and moderate antibacterial activity. , Biopolymers such as PEG and chitosan are used as coating material to modify the surface of IONPs. , These biopolymers consist of antibacterial and biocompatible properties .…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The results indicated that the composite material has good antibacterial activity, which is higher than that of pure silver nanoparticles. It is worth noting that the excessive release of metal ions can lead to cytotoxicity and ultimately damage normal tissues [ 10 , 11 ]. To overcome the above obstacles, it is particularly important to develop a safe and efficient antibacterial strategy.…”
Section: Introductionmentioning
confidence: 99%